Resection of pancreatic neuroendocrine tumors: defining patterns and time course of recurrence. Issue 2 (February 2020) - Dong, Ding-Hui; Zhang, Xu-Feng; Lopez-Aguiar, Alexandra G.; Poultsides, George; Makris, Eleftherios; Rocha, Flavio; Kanji, Zaheer; Weber, Sharon; Fisher, Alexander; Fields, Ryan; Krasnick, Bradley A.; Idrees, Kamran; et al.
Abstract: Background: To define recurrence patterns and time course, as well as risk factors associated with recurrence following curative resection of pNETs. Method: Patients who underwent curative-intent resection for pNET between 1997 and 2016 were identified from the US Neuroendocrine Tumor Study Group. Data on baseline and tumor-specific characteristics, overall survival (OS), timing and first-site of recurrence, predictors and recurrence management were analyzed. Results: Among 1020 patients, 154 (15.1%) patients developed recurrence. Among patients who experienced recurrence, 76 (49.4%) had liver-only recurrence, while 35 (22.7%) had pancreas-only recurrence. The proportion of liver-only recurrence increased from 54.3% within one-year after surgery to 61.5% from four-to-six years after surgery; whereas the proportion of pancreas-only recurrence decreased from 26.1% to 7.7% over these time periods. While liver-only recurrence was associated with tumor characteristics, pancreas-only recurrence was only associated with surgical margin status. Patients undergoing curative resection of recurrence had comparable OS with patients who had no recurrence (median OS, pancreas-only recurrence, 133.9 months; liver-only recurrence, not attained; no recurrence, 143.0 months, p = 0.499) Conclusions: Different recurrence patterns and timing course, as well as risk factors suggest biological heterogeneity of pNET recurrence. A personalized approach to postoperative surveillance and treatment of recurrence disease should be considered.